Optimal X-ray micro-CT image based methods for porosity and permeability quantification in heterogeneous sandstones. Issue 2 (27th June 2020) - Callow, Ben; Falcon-Suarez, Ismael; Marin-Moreno, Hector; Bull, Jonathan M; Ahmed, Sharif
Summary: 3-D X-ray micro-CT (XCT) is a non-destructive 3-D imaging method, increasingly used for a wide range of applications in Earth Science. An optimal XCT image-processing workflow is derived here for accurate quantification of porosity and absolute permeability of heterogeneous sandstone samples using an assessment of key image acquisition and processing parameters: image resolution, segmentation method, representative elementary volume (REV) size and fluid-simulation method. XCT image-based calculations obtained for heterogeneous sandstones are compared to two homogeneous standards (Berea sandstone and a sphere pack), as well as to the results from physical laboratory measurements. An optimal XCT methodology obtains porosity and permeability results within ±2 per cent and vary by one order of magnitude around the direct physical measurements, respectively, achieved by incorporating the clay fraction and cement matrix (porous, impermeable components) to the pore-phase for porosity calculations and into the solid-phase for permeability calculations. Two stokes-flow finite element modelling (FEM) simulation methods, using a voxelized grid (Avizo) and tetrahedral mesh (Comsol) produce comparable results, and similarly show that a lower resolution scan (∼5 µm) is unable to resolve the smallest intergranular pores, causing an underestimation of porosity by ∼3.5 per cent. Downsampling the image-resolution post-segmentation (numerical coarsening) and pore network modelling both allow achieving of a REV size, whilst significantly reducing fluid simulation memory requirements. For the heterogeneous sandstones, REV size for permeability (≥1 mm 3 ) is larger than for porosity (≥0.5 mm 3 ) due to tortuosity of the fluid paths. This highlights that porosity should not be used as a reference REV for permeability calculations. The findings suggest that distinct image processing workflows for porosity and permeability would significantly enhance the accurate quantification of the two properties from XCT.